A study of the leafspot disease of lettuce caused by Stemphylium botryosum Wallr. : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the University of New Zealand, Massey Agricultural College - Slade, Donald Arthur (Massey University, 1961)
Lettuce (Lactuca stavia L) is the most important salad crop and a principal vegetable of New Zealand where in many districts it can be grown out of doors all the year round. Winter lettuce growers commonly plant from 1/2 - 5 acres of lettuce, and a good crop will cut 400 cases an acre. In late winter and early spring when other vegetables are scarce, returns to the grower from lettuce may be as high as 20/- to 60/- a case. Returns per acre from winter lettuce are therefore relatively high compared with other winter crops. The success of this crop is of major importance to the grower who commonly depends on it to cover the high winter and spring labour expenses which usually coincide with a period of low production. From season to season and even from week to week in the same season, the quality and quantity of lettuce available is a direct reflection of the prevailing weather conditions. Weather may act directly on the lettuce plant affecting its rate of maturation, appearance and plant size. Weather may also have a profound indirect effect by providing conditions conducive to disease development. It is well recognised that a disease may reach epiphytotic proportions only if weather conditions are favourable to the causual organism. [From Introduction]
Keywords: Stemphylium; Leaf spots; Lettuce; Diseases pests